2014
DOI: 10.1093/ejo/cju016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-4 on orthodontic tooth movement and associated root resorption

Abstract: IL-4 inhibits tooth movement and prevents root resorption in the mouse model. These results suggest that IL-4 could be used as a useful adjunct to regulate the extent of OTM and also to control root resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…Therefore, we evaluated the effect of the vibration device on root resorption. Consistent with previous findings 4 , 49 , experimental tooth movement under a continuous static force of 15 gf induced root resorption in rats. Dynamic vibration applied with continuous static force also induced a certain degree of root resorption compared with the control group; however, the increase was not significant.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we evaluated the effect of the vibration device on root resorption. Consistent with previous findings 4 , 49 , experimental tooth movement under a continuous static force of 15 gf induced root resorption in rats. Dynamic vibration applied with continuous static force also induced a certain degree of root resorption compared with the control group; however, the increase was not significant.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that some degree of root resorption occurs in almost all patients during orthodontic treatment, ranging from minor to severe 46 48 . In animal models, it was demonstrated that experimental tooth movement by means of both light and heavy forces induced root resorption in mice 4 and rats 49 . Therefore, we evaluated the effect of the vibration device on root resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential 5-µm serial sections were prepared from each paraffin block and the five sections containing the largest root area were chosen and analyzed histomorphometrically, as described previously. 24 , 25 The final value was expressed as the mean of the selected sections. 26 The mesial root was histomorphometrically evaluated on the section containing the full length of the root from the cemento-enamel junction (CEJ) to the apex, by means of a double-headed Olympus BX-41 light microscope equipped with a digital camera (DP25 Olympus) and analysis software (DP2-BSW, Olympus).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 13 studies, all were regarded as non-randomized. The most frequently used animals were rats (11 studies), whereas in two studies mice were used for the experiments (Yoshimatsu et al, 2012 ; Hakami et al, 2015 ). The sample sizes ranged from 24 (Seifi et al, 2003 ) to 132 (Boekenoogen et al, 1996 ) (min-max).…”
Section: Resultsmentioning
confidence: 99%